Pollution of lakes and rivers : A Paleoenvironmental perspective - Smol, John P. (Blackwell / Oxford, 2008)
Contents: There is no substitute for water; Sediments an ecosystemïs memory; Retrieving the sedimentary archive and establishing the geochronological clock: collecting and dating sediment cores